2020
DOI: 10.1111/tpj.14620
|View full text |Cite
|
Sign up to set email alerts
|

Multiple xylosyltransferases heterogeneously xylosylate proteinN‐linked glycans inChlamydomonas reinhardtii

Abstract: Summary Nowadays, little information is available regarding the N‐glycosylation pathway in the green microalga Chlamydomonas reinhardtii. Recent investigation demonstrated that C. reinhardtii synthesizes linear oligomannosides. Maturation of these oligomannosides results in N‐glycans that are partially methylated and carry one or two xylose residues. One xylose residue was demonstrated to be a core β(1,2)‐xylose. Recently, N‐glycoproteomic analysis performed on glycoproteins secreted by C. reinhardtii demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 69 publications
(111 reference statements)
1
17
1
Order By: Relevance
“…When XylT1B was knocked out in addition to XylT1A and Man1A, N-glycans lost one Pent as revealed by mass spectrometric analyses. Immunoblotting results confirmed that b1,2-xylose was lost by knocking down XylT1B in the double mutant instead of a b1,4-xylose, which is attached to an outer mannose residue in C. reinhardtii (Mathieu-Rivet et al, 2013;Lucas et al, 2019). Therefore, it can be concluded that XylT1B is a core XylT.…”
Section: Xylt1b Transfers B12-core Xylose Onto N-glycansmentioning
confidence: 66%
See 2 more Smart Citations
“…When XylT1B was knocked out in addition to XylT1A and Man1A, N-glycans lost one Pent as revealed by mass spectrometric analyses. Immunoblotting results confirmed that b1,2-xylose was lost by knocking down XylT1B in the double mutant instead of a b1,4-xylose, which is attached to an outer mannose residue in C. reinhardtii (Mathieu-Rivet et al, 2013;Lucas et al, 2019). Therefore, it can be concluded that XylT1B is a core XylT.…”
Section: Xylt1b Transfers B12-core Xylose Onto N-glycansmentioning
confidence: 66%
“…The position of the remaining Pent could not be resolved due to a lack of specific antibodies. However, newest data suggest that the additional Pent is a xylose attached to the first or second Hex of the a1,3branch (Lucas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting result is the possible presence of a plant-like N-linked β(1,2)-xylosyltransferase (XYLT). C. reinhardtii is known to have xylose residues linked to the core GlcNAc and the antennas, and a previous study has demonstrated the presence of two xylosyltransferases, named XTA and XTB [129]. The absence of HPAT1 and HPAT3 in this microalga was unexpected, given that this microalga was shown to produce O-arabinose structures [124].…”
Section: Computationally Predicted Distribution Of Microalgal N-and Omentioning
confidence: 72%
“…In microalgae, current knowledge regarding the N-glycosylation processes is available essentially in species belonging to the Chlorophytes (Table 1). Among these, the Chlorophyceae Chlamydomonas reinhardtii and the Trebouxiophycea Chlorella vulgaris have been the most investigated microalgae so far (Mathieu-Rivet et al, 2013;Vanier et al, 2017;Lucas et al, 2018Lucas et al, , 2020Schulze et al, 2018;Mócsai et al, 2019Mócsai et al, , 2020aOltmanns et al, 2020). Concerning microalgae with secondary plastids, the structural data available regarding N-glycans have been obtained from the diatom Phaeodactylum tricornutum (Baïet et al, 2011;Vanier et al, 2015;Lucas et al, 2018) and from the Euglenoid Euglena gracilis (De La Canal and Parodi, 1985;O'Neill et al, 2017).…”
Section: N-glycosylation Pathways In Microalgaementioning
confidence: 99%